Determination of Cefotaxime Sodium in Drugs via the use of Six Source of White LEDs Coupled with One Solar Cell as a Detector using CFI Analyser - Marwah A. Kadhim Al-Banaa (Journal of Global Pharma Technology, 2016)
A direct method is described for the determination of cefotaxime sodium in drugs and pure formulations using six LEDs for turbidimtric measurements and one solar cell as a detector. The method is based on formation of a red-brown precipitate produce via the reaction between cefotaxime sodium with Ce(IV) sulfate at acidic medium. Under the optimum established conditions, the linear range of 0.001-0.3mmol/L along with r of 0.9975, limit of detection (LOD) 35.81ng/sample and precision expressed as relative standard deviation for eight replication measurements at 0.07 and 0.25mmol/L less than 1% were obtained for cefotaxime sodium. The method was successfully applied for the estimation of cefotaxime sodium in three drugs. The newly method using the standard additions procedure and the results have shown that no significant difference between the two methods using ANOVA one way test.Keywords: Cefotaxime sodium, Flow injection analysis, Turbidity.